Dinamika Internal Masyarakat Muslim Penganut Tarekat: (Studi Kasus Terhadap Penganut Tarekat Tijaniyah di Kabupaten Nunukan) - Fitriono, Eko Nani (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The Tijaniyah Order is a way for a salik to get closer to Allah SWT, by carrying out all spiritual forms to be carried out at a station sequentially. The beginning of the emergence of the Tijaniyah Order was in West Java, precisely in Cirebon. The development of the Tijaniyah Order continues to follow the times so that this Order has reached other countries such as Tawau, Malaysia. In this study, the author discusses how the development or internal dynamics of the Tijaniyah Muslim community in Nunukan Regency. The result is that the development of the Tijaniyah Order in Nunukan Regency has been very slow but sure. So that the number of adherents of the Tijaniyah Order in Nunukan Regency is still very small. Because the Tijaniyah Order does not just accept and pay allegiance to someone who still has doubts in his heart. His heart could not yet accept the practices and teachings of the Tijaniyah Order. The practice of dhikr in the Tijaniyah Order educates its members to always be close to Allah both physically and spiritually, so that what is written in the heart and what is said orally, namely dhikr, goes hand in hand continuously and is reflexive. It is meant to resist every ugly scratch in the mind. So as to produce a clear mind, clean from scratches other than Allah. The practice of remembrance is basically the basics of practice that must be developed by members to organize maqamat until they reach the degree of sainthood.